2013 IEEE 10th International Symposium on Biomedical Imaging 2013
DOI: 10.1109/isbi.2013.6556549
|View full text |Cite
|
Sign up to set email alerts
|

Parametric distributions for assessing significance in modular partitions of brain networks

Abstract: Brain networks are often explored with graph theoretical approaches, and community structures identified using modularity-based partitions. Despite the popularity of these methods, the significance of the obtained subnetworks is largely unaddressed in the literature. We present two parametric methods to assess the statistical significance of network partitions, and therefore control against spurious subnetworks that may arise in random graphs, rather than self-organized brain networks. We evaluate these method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been shown that scaled and shifted Gamma distributions can well approximate the Tracy-Widom distribution, either by directly minimizing the difference between the two distributions (Vlok and Olivier (2012)), or by matching their first, second, and third moments (Wei and Tirkkonen (2011); Chiani (2012)). In (Chang et al (2013)) we showed that such an approach led to inferior numerical results than the Tracy-Widom distribution.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that scaled and shifted Gamma distributions can well approximate the Tracy-Widom distribution, either by directly minimizing the difference between the two distributions (Vlok and Olivier (2012)), or by matching their first, second, and third moments (Wei and Tirkkonen (2011); Chiani (2012)). In (Chang et al (2013)) we showed that such an approach led to inferior numerical results than the Tracy-Widom distribution.…”
Section: Discussionmentioning
confidence: 99%